Źródła poparcia wyborczego lokalnych liderów w samorządowych kampaniach wyborczych (na przykładzie kampanii wyborczych prezydentów miast na prawach powiatu w 2010 roku) - Piechota, Grażyna (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2013)
The paper attempts to order and indicate the most important sources of systemic and non-systemic support allowing local leaders to win elections and thereby gain- ing or maintaining power. The study is concentrated solely on the examination of the sources of support for political leaders in cities with district rights in the 2010 elec- tion campaign. The study was financed by a grant from the Ministry of Science and Higher Education obtained for statutory research at the Andrzej Frycz Modrzewski Krakow University in 2012. The paper also makes use of a portion of studies carried out and published earlier on the topic of the processes of political communication of local leaders in the social media (Facebook and political blogs) and on various Internet websites. The paper presents a full account of the results of these studies in the context of political communication in the election process.
The sources of election support for local leaders in election campaigns for local governments (based on the example of the election campaigns of the presidents of cities with district rights in 2010